2021
DOI: 10.1103/physreve.103.033307
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase-field model for surface diffusion and attachment kinetics in the grand-potential framework

Abstract: Grand-potential based multiphase-field model is extended to include surface diffusion. Diffusion is elevated in the interface through a scalar degenerate term. In contrast to the classical Cahn-Hilliard-based formulations, the present model circumvents the related difficulties in restricting diffusion solely to the interface by combining two second-order equations, an Allen-Cahn-type equation for the phase field supplemented with an obstacletype potential and a conservative diffusion equation for the chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 117 publications
(236 reference statements)
0
8
0
Order By: Relevance
“…in which the thermodynamical relation c α = − ∂ψα ∂µ is exploited to arrive at the phase-specific concentration c α (µ, T). Taking the time derivative of equation (8) yields…”
Section: General Pf Model Formulationmentioning
confidence: 99%
“…in which the thermodynamical relation c α = − ∂ψα ∂µ is exploited to arrive at the phase-specific concentration c α (µ, T). Taking the time derivative of equation (8) yields…”
Section: General Pf Model Formulationmentioning
confidence: 99%
“…The model in Sec. 2.6 on the other hand, is composed of coupled second-order conservative and nonconservative equations [30,37,54]. We compute the evolution of order parameters, which are non-conserved via the Allen-Cahn equation ( 23), and secondly the evolution of chemical potential (26), which is based on mass conservation.…”
Section: Comparison Of the Two Approachesmentioning
confidence: 99%
“…This framework has been sucessfully combined with elastic driving forces based on jump conditions [31,32] to model martensitic transformations [12], crack propagation [33][34][35] and the evolution of electric field to study electromigration [36]. It has further been shown that grain boundary diffusion [37] as well as the instability leading to phase separation in the miscibility gap [6] can be effectively modelled. The aim of this work is to show the potentials of both approaches for the numerical screening of promising intercalation electrode materials while also discussing their complementary range of applicability and their limitations due to modeling assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…The interpolation function hff$$ {h}^{\mathrm{ff}} $$ exhibits a monotonic transition between zero and unity. An evident choice would be hff=trueφ˜$$ {h}^{\mathrm{ff}}=\tilde{\varphi} $$, but also other functions meeting the conditions specified in Reference 26 are appropriate. Higher order polynomials in trueφ˜$$ \tilde{\varphi} $$ lead to a steeper transition of hff$$ {h}^{\mathrm{ff}} $$ in interface normal direction η$$ \eta $$.…”
Section: Mathematical Formulationmentioning
confidence: 99%